Mussel directed synthesis of SnO2/graphene oxide composite for energy storage. (2nd November 2021) - Chi, Wenhao; Zou, Zhaoyong; Wang, Wenxuan; Wan, Fuqiang; Ping, Hang; Xie, Jingjing; Wang, Weimin; Fu, Zhengyi
Abstract : A SnO2 /graphene oxide composite with a homogeneous microstructure and enhanced lithium storage performance is synthesized through a natural biological process in living mussels at room temperature. Abstract : A living organism is a complex "biosynthesis factory" for the fabrication of materials under environmentally benign conditions, which is worth studying to extend synthesis techniques. Inspired by the formation process of pearls, living mussels have been used to direct the formation of nitrogen-doped anatase TiO2 . Here, instead of only synthesizing single-phase materials, we extend the technique for the fabrication of a SnO2 /graphene oxide composite. The tin chloride hydroxide hydrate precursor transforms into SnO2 nanocrystals in situ on the surface of graphene oxide with good dispersion and high load to form a homogeneous microstructure under the direction of mussels at ambient temperature. The SnO2 /graphene oxide composite exhibits improved lithium storage performance as the anode of a lithium-ion battery. A stable reversible capacity can be achieved, which is up to 1099 mA h g −1 after 100 cycles at a current density of 100 mA g −1 . This study demonstrates the possibility and practicability of synthesizing anthropogenically useful composite materials in living organisms, which is advantageous to extend synthesis methods and reduce energy consumption.